Attachment and Childhood Maltreatment as Moderators of Treatment Outcome in a Randomized Clinical Trial for Provoked Vestibulodynia. Issue 3 (25th January 2022) - Charbonneau-Lefebvre, Véronique; Vaillancourt-Morel, Marie-Pier; Rosen, Natalie O.; Steben, Marc; Bergeron, Sophie
ABSTRACT: Background: Although distal developmental factors, such as attachment and childhood maltreatment (CM), are associated with the occurrence, severity, and adjustment to provoked vestibulodynia (PVD)—the most prevalent form of vulvodynia—no studies to date have examined whether these variables are related to treatment efficacy in the context of PVD. Attachment and CM may act as moderating variables when examining different treatment modalities, whereby individuals with more insecure attachment orientations (anxiety/avoidance) or a history of CM may benefit less from treatments with higher interpersonal contexts, such as sex and couple therapy—a recommended treatment for PVD. Aim: The present randomized clinical trial (RCT) examined attachment and CM as predictors and moderators of sexual satisfaction, distress, and function at post-treatment and 6-month follow-up while comparing 2 treatments for PVD: Topical lidocaine, and a novel cognitive behavioral couple therapy focused on women's pain and partners' sexuality. Methods: One hundred eight women with PVD were randomized to a 12-week treatment of either lidocaine or couple therapy. Women completed questionnaires at pretreatment, post-treatment, and at a 6-month follow-up. Outcomes: (1) Global Measure of Sexual Satisfaction; (2) Female Sexual Distress Scale-Revised; (3) Female Sexual Function Index. Results: Both attachment and CM were significant moderators of treatment outcomes. At either post-treatment or 6-month follow-up, in the couple therapy condition, women with greater attachment avoidance had poorer outcomes on sexual distress, satisfaction and function, whereas women with higher levels of CM had poorer outcomes on sexual satisfaction and sexual function, compared to women in the lidocaine condition. Clinical Implications: Although these novel findings need further replication, they highlight the importance for clinicians to take into account distal factors, for instance, attachment and CM, when treating sexual difficulties such as PVD, as these variables may affect more interpersonal dimensions of treatment (eg, trust, compliance, etc.) and ultimately, treatment progress. Strengths & Limitations: Using a rigorous RCT study design and statistical approach, this study is the first to examine attachment and CM as moderators in the treatment of sexual difficulties. It is however limited by the use of self-report measures, and further studies are necessary to validate the generalizability of current results to other sexual difficulties. Conclusion: Findings support the role of interpersonal factors in the treatment of PVD and indicate that short-term psychological interventions, such as couple therapy, may be less beneficial for women with antecedents of CM and attachment insecurity.